Erdheim-Chester Disease Masquerading as Multiple Myeloma: A Case Report with Molecular Insights - Deepthi, B; Rukmangadha, N.; Prayaga, Aruna K. (Annals of Pathology and Laboratory Medicine, 2025)
Background: Erdheim-Chester disease is a rare, clonal histiocytic disorder characterized by the accumulation of lipid-laden histiocytes in various organs. Its clinical and radiological presentations are often nonspecific and can closely mimic malignancies such as multiple myeloma. This case is being reported due to its unusual presentation with multiple lytic bone lesions, which posed a significant diagnostic challenge and led to initial consideration of a hematologic malignancy. The report also highlights the importance of histopathological and molecular evaluation in reaching a definitive diagnosis and guiding therapy. Case Presentation: A 64-year-old South Asian male presented with low back pain with itching for 6 months. Laboratory investigations revealed anemia and elevated inflammatory markers but no evidence of monoclonal gammopathy or abnormal plasma cell proliferation. Imaging studies showed multiple mixed lytic-sclerotic lesions involving both axial and appendicular skeleton, initially raising suspicion for multiple myeloma. A bone marrow biopsy and trucut biopsy from a lung lesion showed sheets of foamy histiocytes with interspersed lymphocytes and fibrosis. Immunohistochemistry revealed positivity for CD68 and CD163, suggesting a diagnosis of non-Langerhans cell histiocytosis. Based on these findings, a final diagnosis of Erdheim-Chester disease was established. Conclusion: This case underscores the diagnostic complexities associated with Erdheim-Chester disease, particularly when it presents with destructive bone lesions resembling multiple myeloma. It emphasizes the critical role of tissue biopsy, immunohistochemistry, and molecular analysis in distinguishing this rare entity from more common differential diagnoses. Early recognition and accurate diagnosis are essential, as targeted therapies can lead to significant clinical improvement and alter the disease course.